Il profilo delle nuvole. A Letter to Gianni Celati - Boffi, Guido (Aisthesis, 2025)
The aim is to show that the landscape is a fiction (of course not a reverie). If it is permissible to speak of landscape in the singular, prescinding for a moment from its places, then it must be understood as a kind of both collective thought and affection in which one is immersed. Landscapes belong to their real effects, which orient their views. They belong to the affective perceptions and mental images of those who pass through them. They belong to local communities, their histories and their industriousness, which cannot be brought back into the abstraction of objective data, good anywhere, under any sky. If a landscape is understood in the manner of a physical or patrimonial entity, then it has no chance, its only survival will have to be guaranteed by (green?) profit: Luigi Ghirri and Gianni Celati’s Il profilo delle nuvole invites us to think so.